The relationship between perceived organizational support and insomnia in Chinese nurses: The Serial multiple mediation analysis - Wang, Mei-Fang; He, Qing; Liu, Zhuo; Du, Juan (Frontiers in Psychology, 2022)
Background Nurses are in high-pressure, high-load, and high-risk environment for a long time, and their insomnia cannot be ignored. Insomnia not only has a negative impact on the physical and mental health of nurses, but also on the efficiency and quality of nursing work. Objective The purpose of this study was to investigate the multiple mediating effect of psychological capital, effort-reward ratio, and overcommitment in the relationship between perceived organizational support and insomnia among Chinese nurses. Methods A cross-sectional study has been carried out in a tertiary grade A hospital in Shandong Province, China from June to August 2019. The demographic questionnaire, Perceived Organization Support Questionnaire, Psychological Capital Questionnaire, Chinese version Effort-Reward Imbalance, Questionnaire and Athens Insomnia Scale were used for data collection. SPSS PROCESS 3.4 macro program developed by Hayes was used to test the serial multiple mediation. Descriptive analysis, independent-samples t-test, one-way analysis of variance, Pearson’s correlation analyses, ordinary least-squares regression, and the bootstrap method were used for data analysis. Results 658 valid questionnaires were collected (91.4%). Nurses’ perceived organizational support was positively correlated with psychological capital (r = 0.455, p < 0.001), and was significantly negatively correlated with effort-reward ratio (r = −0.318, p < 0.001), overcommitment (r = −0.328, p < 0.001), and insomnia (r = −0.358, p < 0.001); Psychological capital was negatively correlated with effort-reward ratio (r = −0.275, p < 0.001), overcommitment (r = −0.339, p < 0.001), and insomnia (r = −0.402, p < 0.001), respectively; effort-reward ratio and overcommitment were significantly positively correlated with insomnia (r = 0.379, p < 0.001; r = 0.466, p < 0.001), respectively. In the model of perceived organizational support—psychological capital—effort-reward ratio—insomnia, the overall mediating effect was −0.080 (95%CI: −0.109 −0.058), and the mediating effect of psychological capital was −0.050, accounting for 34.30% of the total effect; the mediating effect of effort-reward ratio was −0.024, accounting for 16.49% of the total effect; the chain mediating effect of psychological capital and effort-reward ratio was −0.007, accounting for 4.49% of the total effect. In the model of perceived organizational support—psychological capital—overcommitment—insomnia, the overall mediating effect was −0.085 (95%CI: −0.109 −0.064), and the mediating effect of psychological capital was −0.042, accounting for 28.64% of the total effect; the mediating effect of overcommitment was −0.029, accounting for 19.81% of the total effect; the chain mediating effect of psychological capital and overcommitment was −0.015, accounting for 10.14% of the total effect. Conclusion Perceived organizational support had direct negative influence on insomnia. Psychological capital and effort-reward ratio/overcommitment acted as chained mediating factor could partially relieve insomnia symptoms related to perceived organizational support. It is suggested to improve the level of organizational support and psychological capital of nurses, and reduce the effort-reward imbalance and overcommitment of nurses, so as to effectively decline and deal with nurses’ insomnia.